2015
DOI: 10.1155/2015/635052
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Autoimmune Encephalomyelitis Development Is Aggravated byCandida albicansInfection

Abstract: Multiple sclerosis (MS) is an inflammatory/autoimmune disease of the central nervous system (CNS) mainly mediated by myelin specific T cells. It is widely believed that environmental factors, including fungal infections, contribute to disease induction or evolution. Even though Candida infection among MS patients has been described, the participation of this fungus in this pathology is not clear. The purpose of this work was to evaluate the effect of a Candida albicans infection on experimental autoimmune ence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 39 publications
1
19
0
2
Order By: Relevance
“…The cellular responses will be characterized by proliferation and differentiation markers (Foxp3, IL‐17, IFNg, GMCSF, …), by flow cytometry and measurements of secreted cytokines. Is the experimental protocol satisfactory?’ The text of the protocol is inspired by models for EAE available in the literature [32,33].…”
Section: Methodsmentioning
confidence: 99%
“…The cellular responses will be characterized by proliferation and differentiation markers (Foxp3, IL‐17, IFNg, GMCSF, …), by flow cytometry and measurements of secreted cytokines. Is the experimental protocol satisfactory?’ The text of the protocol is inspired by models for EAE available in the literature [32,33].…”
Section: Methodsmentioning
confidence: 99%
“…More recently, a possible relationship between MS and Candida species was proposed [57][58][59]. Our research team recently demonstrated that previous infection with Candida albicans, a commensal and opportunistic human pathogen, aggravates the clinical signs of EAE [60].…”
Section: Epidemiological Evidence That Vitd Is Relevant In Msmentioning
confidence: 96%
“…EAE symptoms do not develop in GF mice, but colonizing GF mice with the Th17 promoting bacteria Segmented Filamentous Bacteria (SFB) restores EAE susceptibility (Lee et al, 2011). Similarly, the Th17 promoting fungus Candida albicans has been associated with exacerbated EAE and has been detected in the cerebrospinal fluid of MS patients (Fraga-Silva et al, 2015). Conversely, probiotic mixtures of regulatory T cell-promoting bacteria can dampen neuroinflammation and EAE symptoms (Kwon et al, 2013).…”
Section: Multibiome-host Interactions Influence Immune-mediated Diseamentioning
confidence: 99%